Cultivated and native browse legumes as calf supplements in Ethiopia - Coppock, D. Layne; Reed, J.D. (1992)
Investigates the nutritive value of three important native forages in southern Ethiopia (two browses and one cultivated legume) for possible inclusion in improved feeding systems for calves managed by seminomadic pastoralists. Fruits (pods & seeds) of Acacia tortilis (Forsk.) Hayne subsspirocarpa (Hochst. ex A. Rich) Brenan, leaves of A. brevispica (Harms), and cowpea (Vigna unguiculata (L.) Walp) hay were compared with alfalfa (Medicago sativa L.) hay as protein supplements for calves using two approaches. Sheep fed native grass hay under confinement were used for a controlled evaluation in growth and metabolism trials. Calves grazing dry-season forage under simulated pastoral management provided an evaluation under field conditions. All supplements increased nitrogen intake, growth rate, and conversion of dry-matter intake into liveweight for sheep compared to unsupplemented animals. Calf growth & water intake were increased relative to the control by all supplements except cowpea hay. Compared to alfalfa and cowpea diets, tanniniferous Acacia diets had a negative effect on true N. digestibility, but this was offset by their positive effect on reducing loss of urinary N. The A. tortilis diet had a lower true N digestibility than the A. brevispica diet.